Effectiveness of pre-emptive thoracic epidural analgesia for acute post thoracotomy pain relief: a randomised blinded study - Chowdhury, Anupananda; Choudhury, Dipika; Majumdar, Upasana; Sen, Trina (International Journal of Research in Medical Sciences, 2019)
Background: Thoracotomy is one of the most damaging surgical insults on respiratory mechanics and management of post-thoracotomy pain is a challenge. This study was conducted to compare intensity of postoperative pain, measured by VAS, in patients receiving Pre-emptive TEA compared to patients receiving epidural analgesia during surgical closure. Method: Group A comprised of patients receiving Pre-emptive TEA with 0.1%Ropivacaine and 2 μg/ml fentanyl, 20 minutes before incision. Group B comprised of patients receiving the same drug, during surgical closure. Results: Demographic profile was comparable between both groups. Both groups offered good analgesia, but pre-emptive group took an upper hand upto4th postoperative hour (p<0.05), both at rest and coughing. Beyond 4thhour, analgesic efficacy of both groups was comparable. Conclusion: Pre-emptive technique offered better analgesia over the postoperative technique up to 4th postoperative hour, both at rest and coughing.